Agnes Heller: From Marx to the Dictatorship Over Needs - Beilharz, Peter (2015)
The theory of needs in Agnes Heller is iconic in her work: yet it is also part of the past. This paper revisits her early work (1976) and connects it through to the later, but also pathbreaking idea of the dictatorship over needs (1983). It then aligns the project of dictatorship over needs with van Bremzen’s 2015 work on the dictatorship over food production and consumption . This is claim that the idea of dictatorship over needs remains a privileged optic for the critique of Soviet-type societies, but also to insist that food is a far more fundamental issue that much recent writing in social sciences or humanities allows. The issue of needs persists: even well after Marx, we remain creatures seeking to be rich in needs. The additional focus on food throws all this into a different and more powerful light. It draws Heller’s distant work closer to us, and to the present.